Riparian vegetation variability in natural boreal forests: Lessons for delineating functional forested strips at the margin of aquatic habitats - Philippe Janssen; Audrey Comtois; Marcel Darveau; Bérenger Bourgeois; David Pothier; Monique Poulin (Forest Ecology and Management, 2025)

Visual assessment of tree vigour in Canadian northern hardwood forests: The need for a simplified system - Guillaume Moreau; Malcolm J.L. Cecil-Cockwell; David Pothier; Alexis Achim; Steve Bédard; François Guillemette; John Caspersen (Forest Ecology and Management, 2023)

Predicting Lumber Grade Occurrence and Volume in Sugar Maple and Yellow Birch Logs - Filip Havreljuk; Alexis Achim; David Pothier (Forest Science, 2022)
The North American temperate deciduous forests are an important source of hardwoods sought after by the appearance wood products industries. The purpose of this study was to model the relationships between log characteristics and sawn board attributes in sugar maple (Acer saccharum Marsh.) and yellow birch (Betula alleghaniensis Britt.). We harvested sixty-four sugar maple and thirty-two yellow birch trees from two locations in southern Quebec, Canada, which were then processed into 189 sawlogs and 2,236 boards. We developed statistical models linking log characteristics to the volume recovery of the various lumber grades and color specifications according to the National Hardwood Lumber Association rules. In both species, board grades were strongly related to log length, position of the log in the stem, and small-end diameter and decay of the log. Color classes were related to small-end diameter of the log and red heartwood diameter of the log at both ends for sugar maple, and to log length, diameter of the log at the small-end, and red heartwood diameter at the large-end of the log for yellow birch. These models outperformed a log classification used in practice for predicting lumber volume recovery from different log grades.

Beta diversity of plant community and soil mesofauna along an elevational gradient in a mountainous semi-arid oak forest - Mehdi Heydari; Javad Cheraghi; Reza Omidipour; Majid Mirab-balou; David Pothier (Community Ecology, 2021)

Influence of soil properties and burial depth on Persian oak (Quercus brantii Lindl.) establishment in different microhabitats resulting from traditional forest practices - Mehdi Heydari; Bernard Prévosto; Hamid Reza Naji; Ali Ashraf Mehrabi; David Pothier (European Journal of Forest Research, 2017)

Effects of heartwood formation on sugar maple (Acer saccharum Marshall) discoloured wood proportion - Sharad Kumar Baral; Frank Berninger; Robert Schneider; David Pothier (Trees, 2017)

Processes driving short-term temporal dynamics of small mammal distribution in human-disturbed environments - Julie Martineau; David Pothier; Daniel Fortin (Oecologia, 2016)

Do Boreal Forests Need Fire Disturbance to Maintain Productivity? - Charles Ward; David Pothier; David Paré (Ecosystems, 2014)

Long-term changes in bird community in the unmanaged post-fire eastern Québec boreal forest - Jeovanna Lowe; David Pothier; Ghislain Rompré; Jean-Pierre L. Savard (Journal of Ornithology, 2012)

Using biodiversity deconstruction to disentangle assembly and diversity dynamics of understorey plants along post‐fire succession in boreal forest - Ermias T. Azeria; Mathieu Bouchard; David Pothier; Daniel Fortin; Christian Hébert (Global Ecology and Biogeography, 2011)
Aim The study aims to decipher the co‐occurrence of understorey plant assemblages and, accordingly, to identify a set of species groups (diversity deconstruction) to better understand the multiple causal processes underlying post‐fire succession and diversity patterns in boreal forest. Location North‐eastern Canadian boreal forest (49°07′–51°44′ N; 70°13′–65°15′ W). Methods Data on understorey plant communities and habitat factors were collected from 1097 plots. Species co‐occurrence was analysed using null model analysis. We derive species groups (i.e. biodiversity deconstruction) using the strength of pairwise species co‐occurrences after accounting for random expectation under a null model and cluster analyses. We examine the influence of a set of spatiotemporal environmental variables (overstorey composition, time‐since‐fire, spatial location and topography) on richness of species groups using Bayesian model averaging, and their relative influence through hierarchical partitioning of variance. Results Understorey plant assemblages were highly structured, with co‐occurrence‐based classification providing species groups that were coherently aggregated within, but variably segregated between, species groups. Group richness models indicate both common and distinct responses to factors affecting plant succession. For example, Group 2 (e.g. Rhododendron groenlandicum and Cladina rangiferina ) showed concurrent contrasting responses to overstorey composition and was strongly segregated from Groups 3 (e.g. Clintonia borealis and Maianthenum canadense ) and 4 (e.g. Epilobium angustifolium and Alnus rugosa ). Groups 3 and 4 showed partial similarity, but they differed in their response to time‐since‐fire, drainage and latitude, which were more important for Group 1 (e.g. Ptilium crista‐castrensis and Empetrum nigrum ). A single successional model based on total richness masked crucial group‐level relationships with factors that we examined, such as latitude. Main conclusions By demonstrating the co‐occurrence structure and linking to causal factors, the results from this study characterize both common and distinct responses of understorey plants to biophysical attributes of sites, and potential interspecific interactions, behind non‐random assemblage structure during post‐fire succession. A biodiversity deconstruction approach could offer a concise and explicit framework to gain a better understanding of the complex assembly of ecological communities during succession.

Photosynthetic light response and growth analysis of competitive regeneration after partial cutting in a boreal mixed stand - David Pothier; Marcel Prévost (Trees, 2002)